Job Satisfaction as A mediator: The Impact of Human Security on Organizational Commitment of Academic Staff at Jordanian Universities - Fuad Talafha; Amani Mashhoor Al-Refai; Husam Arman; Ammar Abdallah; Farida Boulesnane; Alaeddin Ahmad (Migration Letters, 2023)
Advancing the education system in developing countries is essential in building creative human capital. Higher education institutions (HEIs) are key actors in any country’s education ecosystem, and their faculty’s organizational commitment is the engine of any development. This paper utilizes structural equation modelling (SEM) to investigate the role of human security and job satisfaction in influencing organizational commitment. A quantitative method used a cross-sectional online research questionnaire to collect the primary data. A sample of (N=356) respondents, who are academic staff at Jordanian universities. The results demonstrated a strong relationship among the aforementioned factors, where human security has a significant positive effect on job satisfaction and organizational commitment. In addition, job satisfaction has a partial mediating effect since there is a direct, significant positive relationship between human security and organizational commitment. The paper recommends that universities’ top management address all human security components to retain its human resources, which is critical in the education sector.